“No data, no problem”? Potential inequities in psychosis among immigrants in the United States - Supriya Misra; Isha Weerasinghe; Lawrence H. Yang; Bizu Gelaye; Margarita Alegría (SSM - Mental Health)
Global research indicates inequities in the incidence, severity, and care of psychosis among immigrants, primarily due to structural and social adversities relative to non-immigrants. However, despite having the world's largest immigrant population, the United States (U.S.) has limited research on this phenomenon. This lack of data obscures potential inequities and presents a missed opportunity to target policies and resources for this population. In this critical analytical review, we briefly summarize the evidence of inequities in psychosis among immigrants in other Western high-income countries, discuss the relevance to immigrants in the U.S. context, identify historical context and contemporary obstacles to studying this phenomenon in the U.S., and recommend strategies to improve research about psychosis among immigrants in the U.S. moving forward. Specifically, effective data collection regarding psychosis among immigrants can be achieved via shifting to person- and community-centered perspectives, leveraging existing federal data systems and funding mechanisms, improving data collection through better tools and collaboration, prioritizing inclusive engagement and recruitment, and broadening conceptions of mental experiences outside of psychiatric diagnoses. However, these investments must center on autonomy and self-determination of immigrants, given the documented harms of coercive care, such as forced treatment of individuals who experience psychosis, which is once again on the rise nationally.